Short-time work: A bridge to employment security or a springboard to unemployment?. (February 2022) - Pavlopoulos, Dimitris; Chkalova, Katja
This article investigates the employment effect of short-time work in the Netherlands during the Great Recession (2009–2011). Short-time work was introduced during the period as a special arrangement with the aim of reducing unemployment hikes by offering firms the possibility of adjusting the working time of specialised workers rather than adjust the size of their workforce. The authors focus on the effect of short-time work at the individual level of the worker and study whether short-time programme participants in surviving firms had a lower job turnover rate and transition rate to unemployment compared to workers who did not participate in the programme. Furthermore, the authors study whether the flexibility policies of the firm had a substantial influence on the effectiveness of short-time work in protecting workers from unemployment. Specifically, they investigate whether the effect of short-time work is related to the intensiveness of its use by the firm and the extensiveness of the use of external flexibility arrangements – i.e. temporary contracts and temporary agency workers – by the firm. For this purpose, the authors apply a discrete-time survival model using a unique dataset with monthly register data from Statistics Netherlands. Participants in the short-time work programme are compared with non-participant workers from firms that used short-time work and workers from firms that did not make use of the programme. The findings indicate that, in surviving firms, short-time work had a positive effect: the risk of unemployment and job separation is, in most cases, lower for short-time work participants than non-participants. Short-time work is most effective in protecting workers from unemployment in firms that extended the use of the programme to many workers and for a relatively small number of hours, and that made either moderate use of temporary agency workers or extensive use of fixed-term contracts.